Comparison of the Intestinal Microbiota During the Different Growth Stages of Red Swamp Crayfish (Procambarus clarkii) - Xie, Mengqi; Zhang, Shiyu; Xu, Lili; Wu, Zhixin; Yuan, Junfa; Chen, Xiaoxuan (Frontiers in Microbiology, 2021)
This study aimed to determine the effect of the growth stage of Procambarus clarkii on their intestinal microbiota. Intestinal samples of five different growth stages of P. clarkii (first instar, second instar, third instar, juvenile, and adult) from laboratory culture were analyzed through the Illumina MiSeq high-throughput sequencing platform to determine the intestinal microbiome of crayfish. The alpha diversity decreased along with the growth of the crayfish, with the relative abundance of the microbiota changing among stages; crayfish at closer development stages had a more comparable intestinal microbiota composition. Comparative analysis by principal component analysis (PCA) and principal coordinate analysis (PCoA) showed that there were significant differences in the intestinal microbiota of crayfish among the different growth stages, except for the first two stages of larval crayfish, and the intestinal microbiota showed a consistent progression pattern from the larval stage to the juvenile stage. Some microbiota showed stage-specificity, which might be the characteristic microbiota of different stages of growth. According to FAPROTAX functional clustering analysis, the three stages of larvae were clustered together, while the juvenile and adult stages were clustered separately according to the growth stage, indicating that in the early stages of larval development, the function of the intestinal flora was similar; as the body grew and developed, the composition and function of the intestinal microbiota also changed.